Multiplicity of Techniques and Its Role in Industrial Product Presentation (Journal of the College of Basic Education, 2026)
This research focuses on the concept of multiplicity of techniques as an integrative approach in industrial design, combining manual representation tools with digital technologies, modeling techniques, rendering methods, rapid prototyping, and interactive display technologies such as Augmented Reality (AR) and Mixed Reality (MR). The aim is to enhance the quality of industrial product presentation and improve the viewer’s perception of form, scale, and functionality.The study stems from an applied educational problem represented by the reliance of some student projects on a single technique whether hand drawing, Computer-Aided Design (CAD), or physical prototyping which weakens visual storytelling and limits the effectiveness of scientific evaluation of the industrial product.The research adopts an applied methodology based on the analysis of selected global case studies as reference models that can be implemented within the design studio environment. Accordingly, a set of evaluative indicators is derived to establish a relationship between the multiplicity of techniques and the quality of product presentation.The study proposes a dual evaluation framework consisting of:Usability, according to the ISO 9241-11 standard, measured through effectiveness, efficiency, and user satisfaction.Visual output quality criteria, including lighting, material representation, composition, visual narrative, and technical quality.Recent studies indicate that integrating CAD technologies with extended reality and 3D printing enhances design teams’ ability to visualize complex products and shortens development cycles. Furthermore, AR and MR technologies support full-scale contextual validation and enable accurate measurement of usability indicators.